Application of fabric phase sorptive extraction with gas chromatography and mass spectrometry for the determination of organophosphorus pesticides in selected vegetable samples. Issue 4 (15th January 2019) - Kaur, Ramandeep; Kaur, Ripneel; Rani, Susheela; Malik, Ashok Kumar; Kabir, Abuzar; Furton, Kenneth G.
Abstract: In the present work, a high‐efficiency and solvent minimized microextraction technique, fabric phase sorptive extraction followed by gas chromatography and mass spectrometry analysis is proposed for the rapid determination of four organophosphorus pesticides (terbufos, malathion, chlorpyrifos, and triazofos) in vegetable samples including beans, tomato, brinjal, and cabbage. Fabric phase sorptive extraction combines the beneficial features of sol‐gel derived microextraction sorbents with the rich surface chemistry of cellulose fabric substrate, which collectively form a highly efficient microextraction system. Fabric phase sorptive extraction membrane, when immersed directly into the sample matrix, may extract target analytes even when high percentage of matrix interferents are present. The technique also greatly simplifies sample preparation workflow. Most important fabric phase sorptive extraction parameters were investigated and optimized. The developed method displayed good linearity over the concentration range 0.5–500 ng/g. Under optimum experimental conditions, the limits of detection were found in the range of 0.033 to 0.136 ng/g. The relative standard deviations for the extraction of organophosphorus pesticides were < 5%. Subsequently, the new method was applied to beans, tomato, brinjal, and cabbage samples. The results from the real sample analysis indicate that the method is green, rapid, and economically feasible for the determination of organophosphorus pesticides in vegetable samples.